Expansion of a stationary retail trading network in Vilnius and the Vilnius district in 1861-1904 - Aelita Ambrulevičiūtė (Lietuvos Istorijos Studijos)
From a local point of view, Vilnius city and its suburbs were chosen to analyze the stationary trading development process. Vilnius, a city that is the center of gubernatorial and general gubernatorial administration, became the biggest Russian imperial North-West Land retail trade center in the 19th century and therefore clearly shows the stationary retail trade net development and citizens' needs changes in the Lithuanian and Byelorussian territories when industrial manufacture extended from the 19th century's second half until the beginning of the 20th century.